PENGARUH PENGGUNAAN OBAT GOLONGAN CALSIUM CHANNEL BLOCKERS (CCB) DIBANDINGKAN ANGIOTENSIN RECEPTOR BLOCKERS (ARB) TERHADAP LUARAN KLINIS PASIEN HIPERTENSI DENGAN GANGGUAN GINJAL DI RSI IBNU SINA BUKITTINGGI - Annisa Rahim; Tika Afriani; Ariesta Kirana Efmisa (LPPM Universitas Mohammad Natsir Bukittinggi, 2026)
Hypertension is a major risk factor for chronic kidney disease (CKD) with a complex bidirectional relationship. Appropriate selection of antihypertensive drugs in patients with hypertension and end-stage CKD is crucial to prevent disease progression and improve clinical outcomes. This study aimed to compare the effectiveness of Calcium Channel Blockers (CCB) and Angiotensin Receptor Blockers (ARB) on changes in blood pressure and kidney function in patients with hypertension and stage 5 CKD at RSI Ibnu Sina Bukittinggi. A descriptive-analytic design with a retrospective approach was employed, involving 30 patients who met the inclusion criteria from a total of 78 patients during the period February 2023–December 2024. Parameters observed included systolic/diastolic blood pressure, serum creatinine, glomerular filtration rate (GFR), and urea levels before and after therapy. The results showed that both therapy groups experienced reductions in blood pressure and improvements in kidney function. The decrease in systolic/diastolic blood pressure for CCB was 14.7/11.4 mmHg, while for ARB it was 14.2/11.2 mmHg. Increases in GFR, reductions in creatinine, and decreases in urea occurred in both groups with no statistically significant differences (p>0.05). In conclusion, CCB and ARB have comparable clinical effectiveness in controlling blood pressure and improving kidney function parameters in patients with hypertension and end-stage CKD.